REALIZATION OF COMPETITIVE GOVERNMENT BUREAUCRACY THROUGH THE REINVENTING GOVERNMENT APPROACH - Afrijal, Afrijal; Herizal, Herizal; Yanza, Fabri; Helmi, Helmi; Kamaly, Nurul; Usman, Bustami (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2024)
This study focuses on the realization of a competitive government bureaucracy through the approach of reinventing government. The slow bureaucracy and low quality of services remain issues that demand the attention of government bureaucrats. This paper aims to provide a comprehensive overview of realizing a competitive bureaucracy by applying the principles of reinventing government. The method used in this paper is qualitative, employing a library research approach. The results of the discussion indicate that reinventing government serves as a concrete solution for government agencies to improve their performance in administration. The flexibility of issues and public needs requires the government to continuously innovate. Enhancing performance systems, capacity, and the quality of government apparatus can serve as the main improvements for realizing a competitive government.